2008
DOI: 10.1111/j.1467-6486.2007.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Real Options, International Entry Mode Choice and Performance

Abstract: Recent scholarship suggests that combining insights from real option theory with transaction cost economics may improve decision-making models. In response to this suggestion we develop and test a model of international entry mode choice that draws from both perspectives. Examining samples of Dutch and Greek firms entering Central and Eastern European markets, we found that adding real option variables to a transaction cost model significantly improved its explanatory power. Additionally, firms that used the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
185
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(201 citation statements)
references
References 67 publications
12
185
1
1
Order By: Relevance
“…Recently, Brouthers (2013) also called for the testing of the moderating impact of institutional variables on transaction cost attributes. Other studies extended findings from TCE studies on FME choices and performance Werner, 2003 andHu, 2002), by combining insights from TCE and real option theories (Brouthers et al, 2008b).…”
Section: Discussion and Some Directions For Future Researchmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, Brouthers (2013) also called for the testing of the moderating impact of institutional variables on transaction cost attributes. Other studies extended findings from TCE studies on FME choices and performance Werner, 2003 andHu, 2002), by combining insights from TCE and real option theories (Brouthers et al, 2008b).…”
Section: Discussion and Some Directions For Future Researchmentioning
confidence: 95%
“…In this context, previous theoretical perspectives have been criticised for over emphasising the sources of uncertainty, i.e. transaction costs, and partner opportunism (TCE) (Brouthers, Brouthers & Werner, 2008b), and lack of experiential knowledge (Uppsala model) (Reuer & Leiblein, 2000). For instance, Schilling and Steensma (2002) suggested that, although threat of opportunism (TCE) and desire to acquire resources (RBT) influence FMEMs, real option rationales may help explain whether and how decision makers vary in their risk aversion to different sources of uncertainty.…”
Section: Real Options Theorymentioning
confidence: 99%
“…For example, the seminal contribution by Johanson and Vahlne (1977) is based on case studies of few Swedish firms, while the more recent paper by Brouthers et al (2008) relies on a survey of Dutch and Greek firms.…”
Section: The Dynamics Of Export and Fdi Entriesmentioning
confidence: 99%
“…These are: (1) organizational structure and culture 19,26 ; (2) types of business strategy 26,28 ; (3) resources available 29,30 ; (4) technological infrastructure and knowledge 31,32 ; (5) market positioning 30,33 ; (6) on-and off-line marketing strategy and objectives 34,35 ; (7) understanding of e-commerce models 36,37 ; (8) nature of products or services 26,33 ; and (9) target market segment and market scope 35,38 . On the other hand, there are seven external influencing factors identified from the literature that may impact strategic decision making.…”
Section: Literaturementioning
confidence: 99%
“…On the other hand, there are seven external influencing factors identified from the literature that may impact strategic decision making. These are: (1) type of industry or sector 26, 33 ; (2) buyers and suppliers 26,39 ; (3) competitors 31,32 ; (4) environmental factors 10,22 ; (5) market trends 40,41 ; (6) consultants 42,43 ; and (7) strategic partners 26,44 .…”
Section: Literaturementioning
confidence: 99%